L’enfant et sa littérature dans la société française - Kovács, Marietta; Montagnon, Beatrix (Verbum – Analecta Neolatina, 2010)
The aim of this paper is to give a systematic overview of the representatives and works of French children and youth literature based on a possible typology set up by the authors. The first section of the study intends to give a definition of children and youth literature, describing the selection criteria of the works which can be included in this category, while the second section of the study briefly outlines the history of French children and youth literature. Publishers have a significant role in reaching the target audience as well as in wide diffusion, which is described in the third section. The fourth section aims to briefly introduce the works of classic and modern authors, picture-book writers and illustrators who are the most well-known in Hungary. In the conclusion, the dimensional changes of the French children and youth literature are highlighted as well as its development into a modern scholarly field providing potential research topics in the future.